The Role of Infill Walls in the Dynamic Behavior and Seismic Upgrade of a Reinforced Concrete Framed Building - De Angelis, Alessandra; Pecce, Maria Rosaria (Frontiers in Built Environment, 2020)
Masonry infill walls are commonly used in the frames of reinforced concrete (RC) buildings around the world. The seismic performance of these buildings is strongly affected by the presence of the infill walls and partitions, as shown by the post-earthquake damage in many cases. The effect of these components is particularly important for RC frame constructions under-designed for seismic actions, that usually are characterized by deformable frames magnifying the contribution of the infill walls to the seismic response. Also the flexibility of the floors could be influenced by the collaboration of the infill walls to the transversal stiffness of the building. The paper addresses the seismic assessment of a typical infilled RC frame building designed only for gravity loads in the 60s in the Southern of Italy that currently is an high seismic zone. The structural identification of the building based on ambient vibration test has been already done pointing out the significant role of infill walls and partitions through the updating of the numerical model. Based on the results of the calibrated model, the effect of the floor flexibility on the dynamic behavior of the structure is discussed and the seismic capacity at Life Safety Limit State (LSLS) is assessed by means of linear dynamic analyses. The effects of the infill walls on the seismic performance of the building are discussed in detail considering a strengthening solution that involves the infill panels as masonry walls cut from the RC columns to avoid the local interaction but strengthened by composite grids in mortar matrix (FRCM).